Popular health surveillance: concepts, experiences and challenges in the Brazilian context - Oliveira, Simone Santos; Mesquita Huet Machado, Jorge; Coradin, Cristiane [UNESP]; Pena, Paulo Gilvane Lopes; Portella, Sergio; Leão, Luís Henrique da Costa (FapUNIFESP (SciELO), 2024)
This article discusses the potential of popular health surveillance (PHS), which articulates notions of social determinants of health, territory, popular education, public participation, intersectionality, feminism and agroecology and is characterized by organization in mutually supportive networks within networks. Public participation enabled by PHS is viewed as a good pathway to bridging the gap between management/academia and territories, through symmetrical dialogue among knowledges, facilitating emancipatory processes. The findings point to the need to overcome the health surveillance approach grounded in the hegemonic model of health centered around top-down control-based actions that disregard local knowledge. In this sense, PHS actions open up possibilities of reconfiguration and promote public participation in the Brazilian National Health System (SUS) by shedding light on intersectionalities of class, gender and race, which are constitutive elements of historical processes of vulnerabilization of the Brazilian population.
Vigilancia popular en salud: conceptos, experiencias y desafíos en el contexto brasileño
Vigilância popular em saúde: conceitos, experiências e desafios no contexto brasileiro
Keywords: Intersectionality; Popular health surveillance; Public participation; Territory; Workers’ health